ANALISIS POLEMIK EUTHANASIA DITINJAU DARI PERSPEKTIF HAK ASASI MANUSIA (PERBANDINGAN EUTHANASIA DI INDONESIA DAN BELANDA) - Natasha Grace; Ida Kurnia (Fakultas Hukum Universitas Tarumanagara, 2021)
Euthanasia is very debatable whether it has to be legalized in Indonesia. Every human being has the right to life. But there is a new idea about human rights. It is called the right to die. A patient in a terminal state should not suffer from their unbearable pain whilst waiting for death. Euthanasia is a medical procedure helping patients with terminal state to die peacefully without any pain. Active euthanasia is illegal in Indonesia according to Article 344 Indonesia’s Penal Code. Passive euthanasia is still allowed in Indonesia according to Minister of Health Regulation Number 37 Year 2014. Euthanasia is allowed in some countries. The Netherlands is the first country in the world to legalized euthanasia. According to The Netherlands Government, to let someone suffer an unbearable pain and in agony whilst waiting for death is very inhuman. Every person has the right to die in peace and without pain. On the other hand, it is against the right to life to do euthanasia on a terminal patient. The function of this research is to compare regulations about euthanasia in Indonesia and The Netherlands and to decide the borderlines of euthanasia in Indonesia. This study uses normative method and qualitative analysis while using statute and comparative approach. The result of the study shows the pros and cons of euthanasia and whether it has to be legalized in Indonesia.